Opportunities of the development of the learning competence of preschool education teachers at workplace as an element of the organizational culture - Smilgiené, Jurgita; Masiliauskiené, Erika (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The results of the conducted research have shown that the meaning of the competence of knowing how to learn is related to the development of personality, ability to find information, and apply it in respective activity. Teachers develop and assess the competence of knowing how to learn through various methods, practical tasks, by stimulating independence. The research has also revealed that the application of the knowledge gained in teacher learning process in everyday activity receives constant evaluations that give added value to the learning process. Positive feedback among teachers and learners has also been mentioned. Among the evaluations there is also a sceptical attitude, the attempt to contradict a teacher’s effort to go beyond the established practice and trying to search for new forms of activity.
Keywords: teacher learning; workplace; organizational culture; development of learning competence; preschool education teacher